Тhe Climate Change Impact on the Gender Security Dimension (International Journal of Contemporary Security Studies, 2023)
Climate change is increasing the gap between security and gender inclusion, ie changing the security dynamics that will be increasingly unfavorable for women and girls in the future. As a vulnerable category, women are often seriously threatened during emergencies. Given the unequal and marginalized position of women in patriarchal and marginalized societies, women's safety and well-being may be further compromised by exposure to natural disasters (shelters in poor settlements, floodplains, conflict zones, seismic areas, etc.), and becoming doubly endangered - by additional marginalization and direct endangerment of security, health, and well-being.The aim of this paper is to review the academic literature related to climate change and the gender security nexus. Relying on the human security concept as a basic theoretical starting point, we aimed to point out the consequences that various aspects of climate change (primarily manifested through natural disasters) negatively affect women. Therefore, the basic methodological tool is the content analysis of relevant academic articles, international documents, and practical policies that address the issue of gender, security, emergencies, and climate change.
Keywords: emergencies, natural disasters, gender inclusion, gender equality, climate change, human security